Urothelial Malignancies of the Upper Urinary Tract A Textbook of Step by Step Management (Springer International Publishing, 2018)
This book addresses all aspects of upper urinary tract urothelial tumors. It represents the first dedicated text to address solely the symptomatology, diagnostic tools, staging, radical and conservative treatment of these tumors. It describes all new diagnostic tools ranging from radiologic to endoscopic and biopsy techniques, antegrade and retrograde methods of conservative endoscopic resection of tumors. Treatment is described in several chapters including open segmental resection, radical total nephroureterectomy, laparoscopic and robotic assisted procedures. Minimally invasive endoscopic approaches are detailed including ureterscopic retrograde and percutaneous antegrade techniques for larger lesions. Intracavitary chemotherapy and immunotherapy and palliative treatments is also covered. The text is richly illustrated and contains links to video clips for visual impact. Chapters also reflect the current technology and new trends on the horizon.